Momentum-space analysis of suprathermal electrons Generation under conditions of gas puffing during Runaway tokamak discharges - Pankratov, I.M.; Bochko, V.Y. (Вопросы атомной науки и техники, 2018)
Using the 2D test particle description, that includes acceleration in the toroidal electric field and collisions with the plasma particles, the generation of suprathermal electrons is analyzed under conditions of working gas puffing close to the Doublet III-D (DIII-D, General Atomics, USA) quiescent runaway shot #152895 parameters. As the result of close collisions, the formation of trapped suprathermal electron population in a nonuniform tokamak magnetic field has been shown.